Particleboard Composite Made from Pinus and Eucalyptus Residues and Polystyrene Waste Partially Replacing the Castor Oil-Based Polyurethane as Binder - Rodrigues, Felipe R. [UNESP]; Bispo, Rodrigo A. [UNESP]; Cazell, Pedro Henrique [UNESP]; Silva, Michael Jones [UNESP]; Christoforo, André L.; Silva, Sergio A.M. [UNESP] (FapUNIFESP (SciELO), 2023)
In Brazil, native forests and replanted forests are poorly managed, and there is concern about reusing plastic residues as well. These two factors play a significant role in the impacts on the environment in the past decades. In this study, the influence of polystyrene (PS) waste partially replacing polyurethane (PUR) as a binder for wood particles (Pinus taeda L. and Eucalyptus saligna) was examined on the physicomechanical and thermal properties of homogeneous particleboards. For the production of particleboard composite, the moisture content of wood particles was set at 2%. A variety of physicomechanical characteristics were evaluated, including density, moisture content, swelling in thickness after 24 hours of immersion in water, rupture modulus (MOR) and elasticity modulus (MOE). Increasing PS relative to PUR decreased MOR and MOE properties in particleboard composite specimens. Thermal analysis shows that replacing PUR with PS in particleboard composite specimens has not adversely affected the thermal stability, and even less its thermal profile of specimens. ABNT NBR standards were exceeded by particleboard composite-based panels, but ANSI standards were met, indicating their potential application. As a result of this study, PS waste could be used as a binder for particleboards and composite materials manufactured from pinus and eucalyptus wood chips in place of PUR.
Keywords: Castor oil-based polyurethane resin; Particleboard composite; physicomechanical properties; Polystyrene residue